2004
DOI: 10.1007/s10329-003-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

Diet and activity in black howler monkeys ( Alouatta pigra ) in southern Belize: does degree of frugivory influence activity level?

Abstract: This study reports on the diet and activity budgets of Central American black howling monkeys ( Alouatta pigra) at Monkey River, Belize. This is a previously unstudied population, close to the southern boundary of the species range, and it provides comparative data on A. pigra from a new study site. Both diet and activity are within the ranges reported for other A.pigra sites and for mantled howlers ( A. palliata). No age-sex differences could be discerned in either diet or activity, though monthly variation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 25 publications
(36 reference statements)
5
64
2
3
Order By: Relevance
“…The prehurricane diet of the population at Monkey River is consistent with that seen in other species of howlers and other populations of A. pigra that show a large degree of seasonality in their diet [Chapman, 1987;Estrada et al, 1999;Julliot, 1994;Serio-Silva, 1997;Silver, 1998;Travers, 2000;Pavelka and Knopff, 2004]. Commonly, the monkeys decrease their consumption of fruit and flowers as well as increase their consumption of leaves during times of year when fruit and flowers are not available, which is necessary because fruit is a preferred food item but is not consistently available throughout the year [Estrada et al, 1999].…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The prehurricane diet of the population at Monkey River is consistent with that seen in other species of howlers and other populations of A. pigra that show a large degree of seasonality in their diet [Chapman, 1987;Estrada et al, 1999;Julliot, 1994;Serio-Silva, 1997;Silver, 1998;Travers, 2000;Pavelka and Knopff, 2004]. Commonly, the monkeys decrease their consumption of fruit and flowers as well as increase their consumption of leaves during times of year when fruit and flowers are not available, which is necessary because fruit is a preferred food item but is not consistently available throughout the year [Estrada et al, 1999].…”
Section: Discussionmentioning
confidence: 50%
“…The 0.25% of time observed feeding on flowers refers to flowers produced by a vine, and this is not reflected in the phenological sampling of tree species. The normal shift in the diet towards consuming a greater proportion of fruit and less leaves in the months of March and April [Pavelka and Knopff, 2004] did not occur following the hurricane because trees were not producing either of these plant parts. Table 3 lists all of the food species eaten by the monkeys during either the preor posthurricane study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our comparison with A. palliata we found that A. pigra have significantly smaller and less variable group sizes than do A. palliata. Mean group size in A. palliata is 15.37 (Glander, 1978;Estrada, 1982Estrada, , 1984Chapman, 1987;Larose, 1996;Stoner, 1996;Estrada et al, 1999;Serio-Silva et al, 1999;Solano et al, 1999;Rodriguez-Luna, 2003;Williams Guillen, 2003;Munoz et al, 2006;Asensio et al, 2007;Dunn et al, 2009;Dunn et al, 2010) and mean group size in A. pigra is 6.83 (Silver et al, 1998;Silver and Marsh, 2003;Pavelka and Knopff, 2004;Pozo-Montuy and Serio-Silva, 2006). Considering the hurricane activity that occurs in the range of A. pigra, low group size could very well represent an adaptation to living in a stochastic environment.…”
Section: Discussionmentioning
confidence: 99%
“…When examining the relationship between fruit consumption and activity patterns we found no consistent differences within or between species in how populations adjust behaviour during periods of fruit shortage. Populations of A. pigra either decreased time spent travelling (from 9.52% to 5.45%), increased time spent inactive (from 69% to 77%) or did not adjust activity patterns in response to seasonal reductions in fruit intake Silver et al, 1998;Pavelka and Knopff, 2004). While some groups of A. palliata also did not show changes in activity that correspond to fruit production, the most common response reported in the literature is an increase in either travel time (from 18.6% to 35.8% in A. palliata in Nicaragua, Williams-Guillen, 2003) or ranging distance (from 114.05 m to 502.88 m for a population in Mexico, Estrada, 1984), which is a response that has never been reported for a population of A. pigra.…”
Section: Behavioural Comparisons Of a Pigra And A Palliatamentioning
confidence: 99%